Topological Magnonics in the Two-Dimensional Van Der Waals Magnet cri3 - Vidal-Silva, N (American Physical Society, 2020)
We report on the magnon spectrum of Kitaev-Heisenberg magnets and extract the parameters to model a two-dimensional CrI3. Our minimal spin Hamiltonian includes a contribution stemming from a Heisenberg, isotropic exchange, and a contribution arising from a Kitaev interaction, anisotropic and frustrated exchange. Our calculations reveal a gap that opens at the K and K′ points and the topological nature of the magnons which lead to the thermal Hall effect. Furthermore, we calculate the magnon spectrum of nanoribbons illustrating the corresponding edge states. © 2020 American Physical Society.